2015
DOI: 10.1111/jpy.12321
|View full text |Cite
|
Sign up to set email alerts
|

Trade‐offs between life‐history traits at range‐edge and central locations

Abstract: The allocation of resources to different life-history traits should represent the best compromise in fitness investment for organisms in their local environment. When resources are limiting, the investment in a specific trait must carry a cost that is expressed in trade-offs with other traits. In this study, the relative investment in the fitness-related traits, growth, reproduction and defence were compared at central and range-edge locations, using the seaweed Ascophyllum nodosum as a model system. Individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 90 publications
1
12
0
Order By: Relevance
“…It is noteworthy that fitness reduction was not accompanied by a significant reduction in the average seed weight ( Table 3 ); confirming the hypothesis that seed size is highly canalized [ 35 ] despite being heritable among genotypes (Gnan et al, 2014). While previous studies have shown that reproductive structures in plants are photosynthetically active [ 23 , 26 , 27 , 36 ], a cost of early reproduction is still implicit in most models of life-history evolution [ 25 , 34 , 37 , 38 , 39 ]; and trade-offs between size and age of reproduction are commonly used as an explanation for lack of response to selection for larger vegetative size [ 40 ] or the maintenance of variation in flowering time [ 8 ]. Our results show that despite the constraint exercised by earlier flowering on plant vegetative size, a cost of early reproduction should not always be assumed, since reproductive structures can sustain significant proportions of the reproductive output.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that fitness reduction was not accompanied by a significant reduction in the average seed weight ( Table 3 ); confirming the hypothesis that seed size is highly canalized [ 35 ] despite being heritable among genotypes (Gnan et al, 2014). While previous studies have shown that reproductive structures in plants are photosynthetically active [ 23 , 26 , 27 , 36 ], a cost of early reproduction is still implicit in most models of life-history evolution [ 25 , 34 , 37 , 38 , 39 ]; and trade-offs between size and age of reproduction are commonly used as an explanation for lack of response to selection for larger vegetative size [ 40 ] or the maintenance of variation in flowering time [ 8 ]. Our results show that despite the constraint exercised by earlier flowering on plant vegetative size, a cost of early reproduction should not always be assumed, since reproductive structures can sustain significant proportions of the reproductive output.…”
Section: Discussionmentioning
confidence: 99%
“…The region has an average sea surface temperature of~16°C, and a tidal range of~6 m. The island is small enough that differences in UV-radiation, temperature and salinity are negligible around its coast. However, wave-exposure and herbivore abundances differ between rocky shores on the island, and because resource allocations are known to differ between A. nodosum stands depending on both biotic and abiotic conditions (Cousens, 1985(Cousens, , 1986Strömgren, 1986;Araújo et al, 2015) fig. 1, see Davies & Johnson, 2006).…”
Section: Site Selectionmentioning
confidence: 99%
“…Araújo et al (2015) showed that A. nodosum individuals in populations close to their southern limit in northern Portugal allocate more resources to reproduction (despite their smaller size, Araújo et al 2014), whereas more investment went into defence in more centrally located populations. It is uncertain whether there is a genetic basis for these differences in strategy as edge populations in A. nodosum, like other fucoids, are generally (strongly) genetically differentiated from central populations (Olsen et al 2010).…”
Section: Demographic Modelsmentioning
confidence: 99%
“…Demographic studies are, however, quite rare in phycology and this is especially true for studies that combine models analysing trade-offs and their effects on population fitness. Demographic matrix models have been constructed for various fucoids (Ascophyllum : Åberg 1992a: Åberg ,b, 1996: Åberg , Araújo et al 2015Fucus: Ang andDeWreede 1993, Araújo et al 2014;Sargassum: Ang 1987, Engelen et al 2005, Engelen and Santos 2009) and a few red seaweeds (Gelidium: Santos 1993, Vieira andSantos 2010;Iridaea: Ang et al 1990, Gracilaria: Engel et al 2001. For the long-lived fucoid, Ascophyllum nodosum, fitness is more sensitive to variation in survival than to variation in growth and fecundity (Åberg 1992a,b).…”
Section: Demographic Modelsmentioning
confidence: 99%